Tomato Cultivars for Production in Florida - Gene McAvoy (EDIS)
IPM-203, a 4-page illustrated fact sheet by G. McAvoy, is part of the Grower’s IPM Guide for Florida Tomato and Pepper Production. It lists tomato varieties currently popular with Florida growers. Published by the UF Department of Entomology and Nematology, December 2007.